1967
DOI: 10.1007/bf01684146
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of 2,4-D in forest litter

Abstract: These studies have shown that 2,4-D is rapidly degraded in forest litter and that the rate of degradation varies with the type of litter, herbicide formulation and the presence of DDT. The degradation of 2,4-D varies slightly in litter from different vegetation types when incubated under similar environmental conditions. Greater variation in herbicide degradation rates may be expected in the field; but this will be due primarily to differences in the site microenvironment, rather than inherent differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…It is almost impossible to calculate the rates of herbicidal breakdown from these studies; although an exception is that of Kirkland & Fryer (1972), who observed the soil half-life times for dichloprop and fenoprop in moist soils at 23°c to be approximately 10 days. These times are in good agreement with the present data (Table 3), Norris (1966) andFoster &McKercher (1973) used [i*C] labelled 2,4-D and 2,4,5-T in their experiments to facilitate analysis. Breakdown of both chemicals was noted in forest litter soil by Norris (1966), with almost 90% ofthe 2,4-D, but only 23% of the 2,4,5-T, being degraded in 2 weeks.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is almost impossible to calculate the rates of herbicidal breakdown from these studies; although an exception is that of Kirkland & Fryer (1972), who observed the soil half-life times for dichloprop and fenoprop in moist soils at 23°c to be approximately 10 days. These times are in good agreement with the present data (Table 3), Norris (1966) andFoster &McKercher (1973) used [i*C] labelled 2,4-D and 2,4,5-T in their experiments to facilitate analysis. Breakdown of both chemicals was noted in forest litter soil by Norris (1966), with almost 90% ofthe 2,4-D, but only 23% of the 2,4,5-T, being degraded in 2 weeks.…”
Section: Resultssupporting
confidence: 91%
“…These times are in good agreement with the present data (Table 3), Norris (1966) andFoster &McKercher (1973) used [i*C] labelled 2,4-D and 2,4,5-T in their experiments to facilitate analysis. Breakdown of both chemicals was noted in forest litter soil by Norris (1966), with almost 90% ofthe 2,4-D, but only 23% of the 2,4,5-T, being degraded in 2 weeks. The studies by Foster & McKercher (1973) indicated that in moist Saskatchewan soils at 26°C the half-life times for ["*C]2,4-D ranged from 14 to 41 days.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The chemical is relatively quickly degraded by soil micro-organisms, but complications may arise through adsorption on to soil articles or mineral soils very low in organic matter. Although there has been much work on the interaction between 2,4-D and clay minerals (Frissel, 1961 ;Weberet al, 1965 ;Bailey and Rothberg 1968), soil organic matter (Norris and Greiner, 1967;Haque and Sexton, 1968) and activated charcoals or carbons (Weber et al, 1965;Ward and Getzen, 1970), there has been no systematic study of the interaction with oxide minerals, which also constitute an important fraction of many soils (Bailey and White, 1970). Hence, the adsorption of 2,4-D on to a well-characterized iron oxide, goethite, was studied here.…”
mentioning
confidence: 99%
“…Norris (1966) and Norris and Greiner (1967) of forest trees: Douglas; fir, big leaf maple, vine, maple, Ceanothus and ret; alder. These little samples were treated with 3 lb/acra equivaleat of (1) and 3% at 70, 85 and 100 o F, respectively.…”
Section: Soilsmentioning
confidence: 99%